P3.293 Condydav: Prospective Observational Study of Patients with External Genital Warts(EGWs)Consulting in STI Clinics in France. (13th July 2013) - Chanal, J; Fouéré, S; Oria, F Yassir; Spenatto, N; Bouscarat, F; Picot, E; Aynaud, O; Janier, M; Dupin, N
Abstract : In this prospective, observational study, we analysed clinical features and treatments between January, 1 2011 and March, 31 2011 of patients consulting for EGWs in 15 STI clinics through France. 372 males and 111 women were included; mean age 31.2 years old. Women were younger than men (31.7 and 28.9 y.o respectively p < 0.05). 414 (85.7%) were heterosexuals, 13 bisexuals and 54 (11.2%) homosexuals; mean age at first sexual intercourse: 17 y.o. Males reported more sex partners in the last 12 months (more than 3 partners in 32.6% versus 11.9% p < 0.01). In males, 230 had an involvement of the penis alone and 46 had an involvement of the anus alone. 76 patients had EGWs of the anus, among them 26 were MSM. In females, 76 had an infection of the vulva alone and 22 a co-infection vulva and anus. Concerning cervical cancer screening, 13 had never been tested (mean age 24.8 y.o. [17–40]); mean delay for the last screening: 12 months [1–108]. Three women have been vaccinated against HPV. 3 males were newly diagnosed HIV positives and 8 for syphilis (7 were MSM RR: 50). In females, 2 patients were HIV positives and 13% had an infection by Chlamydia trachomatis (11/84 not known: 27). Women were significantly more treated with Imiquimod (35% Vs 19.9% p < 0.001).